Study of dynamics and rigidity of multifunctional coating of protective element of aircraft - A. V. Kupryashov (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
In this work using a finite element study the author has numerically solved the problem of the dynamic behavior of a multifunctional coating of an aircraft protective element. The researcher conducted the simulation using the Femap with NX Nastran software package, The result of the modal analysis is the values and patterns of natural and secondary vibration modes of the multifunctional coating of the protective element of the aircraft using a special module the author has determined the distribution of effective modal masses in tabular form, Also, as a result of calculations, the author of the article obtained the value of the structural rigidity of the protective coating, The results presented in this work allow us to analyze the behavior of protective systems and structural elements of an aircraft with a multifunctional coating applied to the outer surface in real operating conditions, The design team can use the research results of this article in order to increase the efficiency of the development of a new structures and structures of a composite coating for multifunctional purposes, protective elements and materials for space technology